Practicality of an Android Based Chemistry Adventure Game as a Chemical Bond Learning Media - Valdo Ayona; Rusly Hidayah (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2021)
The purpose of this study is to test the development of a proper Chemistry Adventure Game as an android-based game media on Chemistry Bond material at MA Negeri 2 Mojokerto. Practicality. Practicality is obtained from students' observation and questionnaire responses. The research method used is a research and development body carried out until practicality of android-based game media for students. Practicality test at X MIPA 1 class MA Negeri 2 Mojokerto. The data obtained from the practicality of the media Chemistry Adventure Game (1) 86,3% students, activity with a very practical category, (2) 87,88% questionnaire responses with a very practical category. Based on the results of the study, it can be concluded that the developed Chemistry Adventure game is suitable for use as a learning media.